Selective reactivation of human herpesvirus 6 in patients with autoimmune connective tissue diseases. Issue 11 (27th August 2013) - Broccolo, Francesco; Drago, Francesco; Cassina, Giulia; Fava, Andrea; Fusetti, Lisa; Matteoli, Barbara; Ceccherini‐Nelli, Luca; Sabbadini, Maria Grazia; Lusso, Paolo; Parodi, Aurora; Malnati, Mauro S.
Abstract Viral infections have been associated with autoimmune connective tissue diseases. To evaluate whether active infection by Epstein–Barr virus (EBV), cytomegalovirus (CMV), human herpesvirus (HHV)‐6, ‐7, ‐8, as well as parvovirus B19 (B19V) occur in patients with autoimmune connective tissue diseases, viral DNA loads were assessed in paired samples of serum and peripheral blood mononuclear cells (PBMCs) of 115 patients affected by different disorders, including systemic sclerosis, systemic, and discoid lupus erythematosus, rheumatoid arthritis, and dermatomyositis. Two additional groups, patients affected by inflammatory diseases (n = 51) and healthy subjects (n = 58) were studied as controls. The titers of anti‐HHV‐6 and anti‐EBV antibodies were also evaluated. Cell‐free HHV‐6 serum viremia was detected in a significantly higher proportion of connective tissue diseases patients compared to controls (P < 0.0002); a significant association between HHV‐6 reactivation and the active disease state was found only for lupus erythematosus (P = 0.021). By contrast, the rate of cell‐free EBV viremia was similar in patients and controls groups. Cell‐free CMV, HHV‐8, and B19V viremia was not detected in any subject. Anti‐HHV‐6 and anti‐EBV early antigen IgG titers were both significantly higher in autoimmune diseases patients as compared to healthy controls, although they were not associated with the presence of viremia. EBV, HHV‐6, ‐7 prevalence and viral load in PBMCs of patients with connective tissue diseases and controls were similar. These data suggest that HHV‐6 may act as a pathogenic factor predisposing patients to the development of autoimmune connective tissue diseases or, conversely, that these disorders may predispose patients to HHV‐6 reactivation. J Med. Virol. 85:1925–1934, 2013. © 2013 Wiley Periodicals, Inc.